Effects of changing net design on the impacts of motorized push net fishery in Iloilo River tidal inlet - Bantiquete, Alvin Hallares (University of the Philippines Visayas, 2019)
This study was conducted to test the differences on the catch composition in terms of speciescomposition, size composition, relative abundance, and relative frequency of occurrence of motorized push net in Iloilo River tidal inlet after modification in gear design such as mesh geometry, mesh size and net type. This study evaluated the impacts of commonly used and modified designs to the parameters of fish population dynamics in Iloilo River tidal inlet that will contribute to use of Ecosystem approach to Fisheries Management (EAFM) in the area. Six (6) designs including the commonly used design where tested during the normal operation hours of motorized push net in the area. Mounted on a boat with 16 Hp engine, the gear " pushed" at the speed of 1.91.9 + 0.4 kph for 10 minutes. Modified covered cod end method was used to determine the selectivity of each designs where Cover A covered the gear mothcodend portion, Cover B covered the body-codend portion while Cover C covered only the codend. A total of twenty-one (21) families were retained throughout the study period.Results showed that Family Penaeidae dominated at all other families with >80% relative abundance and weight across treatment. In design 20/10 D-KL or the original design, F.Penaeidae has a relative abundance and relative weight of 94.92 + 5.24% and 88.65 + 11.65%, respectively. The same observations were noted on modified designs indicating that the gear is suited for capturing F. Penaeidae regardless of the modifications. Additionally, the L50 on the mouth, body, and codend of the original design where almost the same but decreasing invalue on the modified designs. Overall, motorized push nets designs with bigger mesh size regardless of the mesh geometry and material used retained bigger and heavier penaeid. Theuse of existing motorized push net design is not recommend as the current design is an environmental liability.